2022
DOI: 10.3390/ijms23169241
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Chelidonium majus L. Latex and Its Components on HPV Reveal Insights into the Antiviral Molecular Mechanism

Abstract: Yellow-orange latex of Chelidonium majus L. has been used in folk medicine as a therapeutic agent against warts and other visible symptoms of human papillomavirus (HPV) infections for centuries. The observed antiviral and antitumor properties of C. majus latex are often attributed to alkaloids contained therein, but recent studies indicate that latex proteins may also play an important role in its pharmacological activities. Therefore, the aim of the study was to investigate the effect of the crude C. majus la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…The MS spectra ( Figure S2 ) indicate the presence of numerous molecules, some of which were detected and assigned to different chemical classes (alkaloids, amino acids, phenolic acids, flavonoids, carotenoids, organic acids, fatty acids, sterols, and others) that corroborate the literature results [ 6 , 7 , 11 , 15 , 31 , 33 , 38 , 40 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The MS spectra ( Figure S2 ) indicate the presence of numerous molecules, some of which were detected and assigned to different chemical classes (alkaloids, amino acids, phenolic acids, flavonoids, carotenoids, organic acids, fatty acids, sterols, and others) that corroborate the literature results [ 6 , 7 , 11 , 15 , 31 , 33 , 38 , 40 , 42 , 43 ].…”
Section: Resultssupporting
confidence: 87%
“…Numerous research studies have been conducted on the chemical composition and pharmacological activity of Chelidonium majus . Most of these studies have focused on specific phytoconstituent categories found in certain parts of the plant [ 3 , 4 , 5 , 6 , 7 , 8 , 10 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig latexes are more effective natural therapeutic antibacterial agents against pathogenic bacteria [34]. The antiviral properties of C. majus latex are due to both the alkaloids and the proteins it contains, which affect different stages of the virus reproduction cycle [35]. There are so many herbal botanicals that can fight against termites in fields and vegetation [36].…”
Section: Introductionmentioning
confidence: 99%
“…One pharmaceutically important species belonging to Papaveraceae is Chelidonium majus , or Greater Celandine, which is a common herbaceous plant found worldwide, mostly across Europe and East Asia and introduced to North and South America, Australia, and New Zealand. Its metabolite profile includes compounds like benzylisoquinoline alkaloids (e.g., chelidonine, sanguarine, coptisine, berberine, protopine), flavonoids, phenolic acids, unsaturated fatty acids, carotenoids, saponins, and defense-related proteins. ,, Extracts have been used against skin ailments, like eczema, corns, Tinea infections, and tumors of the skin, but also for liver and biliary disorders and as a chalogogue . Moreover, it possesses antiviral properties utilized in traditional folk medicine to remove papillae or warts from the skin, which result from human papilloma virus infection. , Alkaloids and flavonoids produced by this plant have shown strong antimicrobial activity; however, antimicrobial peptides from this plant have remained largely unexplored.…”
mentioning
confidence: 99%